Grant opportunities of the European commission Single Market Program (Economics and region, 2023)
The article discusses the grant opportunities of the European Commissions Single Market Program (SMP). Its goals, priorities and destinations are given. The main components of the program are named, which are relevant for Ukraine and are aimed at: strengthening the competitiveness and sustainability of SMEs and the development and dissemination of statistics in Europe at a high level. It has been demonstrated that the accession of Ukraine to the European program "Single Market Program" opened Ukrainian enterprises access to sub-programs in the following main areas: promotion of entry of SMEs to foreign markets - consultations on export-import of SMEs in the EU and in general; improvement of conditions for maintenance at the level of competitors - including promotion of internationalization of clusters, identification and elimination of unnecessary regulatory barriers; formation of business culture - educational programs, sectoral trainings, seminars, exchange programs, internships, etc. The article provides an overview of grant opportunities within the Single Market Program for representatives of small and medium-sized enterprises. Emphasis is placed on the fact that the Single Market Program is considered the largest global European program for 2022-2027. It was concluded that representatives of small and medium-sized enterprises in Ukraine, thanks to the Single Market Program, have the opportunity not only to use an integrated package of advice on how to implement innovations and grow at the international level, to participate in joint cluster initiatives, but also to attract grant resources from of the European Innovation Council and within the Erasmus for Young Entrepreneurs project. As a conclusion, it is emphasized that the use of the tools of the Single Market Program by Ukrainian entrepreneurs will contribute to increasing their competitiveness and sustainability, and the non-competitive basis of receiving grants by national statistical institutes and other national bodies will contribute to the creation and dissemination of high-quality European statistics.
Keywords: Single Market Program; Single Market Program grants; Single Market; grants for SMEs; grants for business